EL control interno de la administración financiera como medio para el cumplimiento de las normas y sus obligaciones en el Gobierno Autónomo Descentralizado Municipal del cantón Durán, año 2014. - Velasco Martínez, Galo Tomás (2016)
This research was developed with the aim of reducing the risk of internal control in the financial area of the Autonomous Government Decentralized Municipal – Canton Duran, by assessing controls over the processes by designing questionnaires, indicators and tests compliance based on the COSO I methodology and existing legislation. We proceeded to run the assessment under the approval of the highest authority, revealing the weaknesses of the administrative and financial management in 23 findings, the same were summarized and weighted in a risk matrix, detailing the highest risks deemed critical in the internal control report that will be delivered to the highest authority and management of the municipality with the aim that the recommendations are implemented in the institution to improve management effectiveness.